Current perspectives on the dynamics of antibiotic resistance in different reservoirs - Caniça, Manuela (2020)
This work was presented, in part, as an opening lecture plus a keynote at the TEMPH2014-Trends in Environmental Microbiology for Public Health, Lisbon, Portugal